Art Education for Sustainable Development: Transforming Youth Unemployment to Productivity in Seme Border Communities, Nigeria - Adewale, Adekoya Bisola; Peter, Gandonu Sewanu; Oladatun, Oluwa Nurusiq; Olayinka, Azeez Razaq; Ibrahim, Oridola Adeola; Adisa, Shidi Yusuf (Jurnal Karya Abdi Masyarakat, 2025)
The Seme Border area in Nigeria is a strategic Nigeria–Benin trade corridor; however, local youth continue to experience high unemployment, limited access to skills training, and declining engagement with local arts and cultural practices. This condition reflects a gap in community empowerment programmes that integrate economic capacity building with cultural sustainability in border communities. This community service activity aims to empower youth in the Seme Border communities through art education grounded in the Education for Sustainable Development (ESD) framework, with a focus on economic improvement, cultural preservation, and community resilience. The activities were conducted in Seme Border communities, targeting local youth as primary beneficiaries and involving local artists and craftsmen as community partners. The solution offered consisted of participatory mentoring and hands-on learning in traditional arts and crafts that integrate creative skill development with local cultural values. A participatory, action-based approach using qualitative methods was employed to support collaborative learning between the service team and the community. Data were collected through interviews and practical craft-learning sessions with artists, craftsmen, and youth participants, and analyzed thematically to evaluate the implementation process and outcomes. The results indicate that art education not only equips youth with marketable skills in arts and crafts but also revitalizes indigenous heritage, fostering pride and identity. Challenges such as limited resources and policy neglect highlight the need for public–private partnerships to scale community-based art learning programmes. This community service activity concludes that art education is a vital yet underutilized tool for reducing youth restiveness and promoting sustainable growth in border communities.